Terminal value problem for causal differential equations with a Caputo fractional derivative - Yakar, Coskun; Arslan, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this pap er, we have given new definitions and obtained the unique solution of a fractional causal terminal value problem by combining the technique of generalized quasilinearization in the sense of upper and lower solutions.
Keywords: Causal operator; terminal value problem; Caputo fractional derivative; quasilinearization method; quadratic convergence; upper and lower solutions